The transmitted HIV-1 subtype C: characterization of the transmitted/founder full-length virus genome and the influence of early immune selective pressure on virus replication - Abrahams, Melissa-Rose Hilda (Department of Clinical Laboratory Sciences, 2015)
Includes bibliographical references.